Perceived sources of stress amongst final year dental under graduate students in a dental teaching institution at Bangalore, India: A cross sectional study - A G Harikiran; J Srinagesh; K S Nagesh; N Sajudeen (Wolters Kluwer Medknow Publications, 2012)
Background: Dental schools are known to be highly demanding and stressful learning environments. Dentistry involves an acquisition of required academic, clinical and interpersonal skills during the course of learning. Practicing dentistry requires clinical skills and patient management skills, which also add to the stress perceived by the students. Identifying sources of stress represents the crucial first step towards advocating policy changes and strategies to alleviate the stressors and enhance students' stress coping skills. The aim of this study was to identify self-reported sources of the stress among the final year [4 th year] dental undergraduate students in a Dental Teaching Institution in Bangalore, India. Materials and Methods: A 38 items, 4-point Likert Scale item modified Dental Environmental Stress (DES) questionnaire, addressing 5 stressor domains (living accommodation, interpersonal relationships, academics, clinical skills and miscellaneous) was administered to all final year undergraduate dental students of the Institution. Items and domains were considered to be perceived as "stressful", when students classified them as 'slightly', 'moderately' or 'severely stressful'. Descriptive and bivariate analyzes based on chi square tests were performed. Results: Out of the 38 items, 19 items were reported to be "stressful" by >70% of the students. Of these, examinations, difficulty in managing difficult cases, lack of patient co-operation, difficulty and amount of course work and completing clinical requirements were reported to be "stressful" by >85% of the students. Personal physical health, difficulty in making friends, staying with roommates, narcotic substance dependencies were least commonly reported to be "stressful". Discussion and Conclusion: The stress provoking factors among >70% of the students are quite similar to those reported by the researchers' worldwide. Curricular changes, student support mechanisms at departmental/institutional level with appropriate policy changes need to be considered to assist the students in coping with identified stressors.